Biomechanical and biochemical outcomes of porcine temporomandibular joint disc deformation. (April 2016) - Matuska, Andrea M.; Muller, Stephen; Dolwick, M.Franklin; McFetridge, Peter S.
Highlights: Structure–function relationships were evaluated in deformed porcine TMJ discs. Deformed discs had lower tensile and higher compressive modulus. Deformed discs had greater cellularity and areas of hyperplasia. Abstract: Objective: The structure–function relationship in the healthy temporomandibular joint (TMJ) disc has been well established, however the changes in dysfunctional joints has yet to be systematically evaluated. Due to the poor understanding of the etiology of temporomandibular disorders (TMDs) this study evaluated naturally occurring degenerative remodeling in aged female porcine temporomandibular joint (TMJ) discs in order to gain insight into the progression and effects on possible treatment strategies of TMDs. Design: Surface and regional biomechanical and biochemical properties of discal tissues were determined in grossly deformed (≥Wilkes Stage 3) and morphologically normal (≤Wilkes Stage 2) TMJ discs. Results: Compared to normal disc structure the deformed discs lacked a smooth biconcave shape and characteristic ECM organization. Reduction in tensile biomechanical integrity and increased compressive stiffness and cellularity was found in deformed discs. Regionally, the posterior and intermediate zones of the disc were most frequently affected along with the inferior surface. Conclusions: The frequency of degeneration observed on the inferior surface of the disc (predominantly posterior), suggests that a disruption in the disc-condyle relationship likely contributes to the progression of joint dysfunction more than the temporodiscal relationship. As such, the inferior joint space may be an important consideration in early clinical diagnosis and treatment of TMDs, as it is overlooked in techniques performed in the upper joint space, including arthroscopy and arthrocentesis. Furthermore, permanent damage to the disc mechanical properties would limit the ability to successfully reposition deformed discs, highlighting the importance of emerging therapies such as tissue engineering.